2001
DOI: 10.1007/s007750100222
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an iron-nickel hydrogenase from Thermococcus celer

Abstract: Thermococcus celer cells contain a single hydrogenase located in the cytoplasm, which has been purified to apparent homogeneity using three chromatographic steps: Q-Sepharose, DEAE-Fast Flow, and Sephacryl S-200. In vitro assays demonstrated that this enzyme was able to catalyze the oxidation as well as the evolution of H2. T. celer hydrogenase had an apparent MW of 155,000+/-30,000 by gel filtration. When analyzed by SDS polyacrylamide gel electrophoresis a single band of 41,000+/-2,000 was detected. Hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The genome is predicted to encode genes for amino acid transferases and glutamate dehydrogenase, which are both necessary for the fermentation of amino acids ( 16 ). Predicted Ni-Fe hydrogenase complexes and sulfhydrogenases are present in the genome, consistent with the general metabolic capability of Thermococcus spp ( 17 19 ).…”
Section: Announcementsupporting
confidence: 64%
“…The genome is predicted to encode genes for amino acid transferases and glutamate dehydrogenase, which are both necessary for the fermentation of amino acids ( 16 ). Predicted Ni-Fe hydrogenase complexes and sulfhydrogenases are present in the genome, consistent with the general metabolic capability of Thermococcus spp ( 17 19 ).…”
Section: Announcementsupporting
confidence: 64%
“…This type of hydrogenase is only found in archaea and bacteria, where they catalyze either hydrogen oxidation or production. Among them we can find the soluble hydrogenases produced by nitrogenfixing cyanobacteria and bacteria (Bothe et al, 2010), the membrane bound hydrogen-producing enzyme first described in the hyperthermophile Pyrococcus furiosus (Sapra et al, 2003), and the tetrameric hydrogenases found in some hyperthermophiles such as Thermococcus celer (Blamey et al, 2001). Many hydrogenases from this family use NAD(P) or other soluble cofactors such as coenzyme F 420 .…”
Section: Applicationsmentioning
confidence: 99%
“…In this manuscript, we described the gene analysis, purification, and characterization of a cytosolic NiFe-hydrogenase from T. kodakaraensis KOD1. So far, there have been a number of reports on the purification and characterization of cytosolic hydrogenases from hyperthermophilic archaea belonging to the order Thermococcales (3,5,21,29,47). A comparison of their properties with those of the T. kodakaraensis hydrogenase is shown in Table 1.…”
Section: Localization Of T Kodakaraensis Hydrogenasementioning
confidence: 99%
“…This is particularly the case for hydrogenase, as a soluble, thermostable hydrogenase could potentially provide a stable biocatalyst for hydrogen production (43). Accordingly, cytosolic hydrogenases have been identified and studied from various hyperthermophiles, including the archaea Pyrococcus furiosus (19), Thermococcus litoralis (29), Thermococcus stetteri (47), and Thermococcus celer (3) and the bacterium Thermotoga maritima (40). The archaeal enzymes have all been found to be NiFe-hydrogenases, while the enzyme from T. maritima was an Fe-only hydrogenase.…”
mentioning
confidence: 99%